Recommendations for utilization of the paracorporeal lung assist device in neonates and young children with pulmonary hypertension. (21st February 2016) - Gazit, Avihu Z.; Sweet, Stuart C.; Grady, R. Mark; Boston, Umar S.; Huddleston, Charles B.; Hoganson, David M.; Shepard, Mark; Raithel, Steve; Mehegan, Mary; Doctor, Allan; Spinella, Philip C.; Eghtesady, Pirooz
Abstract: The management of decompensating critically ill children with severe PH is extremely challenging and requires a multidisciplinary approach. Unfortunately, even with optimal care, these children might continue to deteriorate and develop inadequate systemic perfusion and at times cardiac arrest secondary to a pulmonary hypertensive crisis. Tools to support these children are limited, and at times, the team should proceed with offering extracorporeal support, especially in newly diagnosed patients who have not benefitted from medical therapy prior to their acute deterioration, in patients with severe pulmonary venous disease and in patients with alveolar capillary dysplasia. Currently, the only approved mode for extracorporeal support in pediatric patients with PH eligible for lung transplantation is ECMO. To decrease the risks associated with ECMO, and offer potential for increased duration of support, extubation, and rehabilitation, we transitioned four small children with refractory PH from ECMO to a device comprising an oxygenator interposed between the PA and LA. This work describes in great detail our experience with this mode of support with emphasis on exclusion criteria, the implantation procedure, and the post‐implantation management.